In, out and through digital worlds. Hybrid-transitions as a space for children's agency. Issue 1 (2nd January 2020) - Scollan, Angela; Farini, Federico
ABSTRACT: A rich tradition of pedagogical and psychological research has explored the impact of technology on the cognitive and social development of the child. However, little research has focused on the implications of the use of digital technologies in educational settings for children's agency. This article introduces hybrid-transitions as a theoretical tool to conceptualise transitions between the use of digitally enhanced and non-digitally enhanced experiences as dense social spaces where young children show agency in the construction and co-construction of knowledges. Hybrid-transitions refers to children's movement from the immersion in digitally-enhanced experiences generated by educational technologies to non-digitally mediated interactions with peers or adults. This article argues, with the support of examples, that during hybrid transitions digital experiences are shared via personal narratives linking ideas, experiences and emotions. Individual narratives are 'interlaced' in co-constructed group narratives authored by the children through face to face interactions. The interactive authorship of interlaced narratives is discussed as a form of agency, as it includes making choices regarding action and understanding of action. This article intends to promote attention to hybrid-transitional spaces among adults who work in educational settings where digital technologies are utilised.